Menjadi Guru Profesional Yang Di Idolakan Peserta Didik - Maftuhah (Jurnal Pendidikan Islam, 2022)
The role of the teacher at school is as a parent for students. Where the teacher must act as a role model so that the learning atmosphere becomes fun according to what is expected. Who does not want to be a teacher idolized by students, it seems that all teachers will expect this. However, do we know that the more we ask to be idolized by students, the further away we will be from the criteria for teachers who are worthy of being idolized by students, if being a teacher idolized by students is our main goal, then as a teacher there is no such thing as professionalism anymore. only obey what students want and what students want. Being a teacher who is idolized by students also does not mean obeying everything the students want or want. Because if the teacher obeys all the wishes of the students, it might even make them out of the goals and activities of the teaching and learning process.